Microorganismos asociados a enfermedades foliares en plantaciones de Eucalyptus spp., de la provincia de Misiones - Dummel, Delia Marlene; Agostini, Juan Pedro; Eskiviski, Edgar Rafael (Facultad de Ciencias Forestales, UNaM. EEA Montecarlo , INTA. Colegio de Ingenieros Forestales de Misiones (Coiform.), 2023)
The Eucalyptus spp. plantations in Misiones is the 10% of the total forestry area implanted in the province, which is increasing due to the demand of wood industry, post manufacturing, and cellulose pulp. The work carried out in the plant protection laboratory of INTA EEA Montecarlo, allowed to identify pathogens associated with foliar diseases, these are: Bacteriosis (23%), Cylindrocladium spp. (19%), Theratosphaeria epicoccoide (19%), Pestalotia spp. (14%), Alternaria spp. (9%), Theratosphaeria pseudoeucalipti (8%), Mycosphaerella spp. (4%), Puccinia psidii (4%), y Harknesia spp. (3%). It is the first report of Alternaria spp. in Eucalyptus spp. plantations in Misiones.